2011
DOI: 10.1007/s10545-011-9435-0
|View full text |Cite
|
Sign up to set email alerts
|

Newborn screening for lysosomal storage diseases: an ethical and policy analysis

Abstract: The traditional focus of newborn screening (NBS) is testing infants for medical conditions like phenylketonuria (PKU) that may cause significant morbidity or mortality unless treatment is initiated early. Although the Wilson and Jungner criteria were not designed specifically for NBS, the public health screening criteria have been used, with some modifications, to justify what conditions are included in a universal NBS panel. These criteria are being challenged by platform technologies like tandem mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 52 publications
(58 reference statements)
1
38
0
Order By: Relevance
“…61,62,65 Several ethical concerns have been raised by the ACHDNC in their responses to proponents of LSD nominations (see above) and by others. 72 A recurring concern of NBS for LSDs is the fact that cases identified as late-onset or mild variants of disease outnumber cases that may require initiation of treatment shortly after birth. As has been observed for Krabbe disease, the result of such cases is frustration both for the affected families and for follow-up care providers.…”
Section: Discussionmentioning
confidence: 99%
“…61,62,65 Several ethical concerns have been raised by the ACHDNC in their responses to proponents of LSD nominations (see above) and by others. 72 A recurring concern of NBS for LSDs is the fact that cases identified as late-onset or mild variants of disease outnumber cases that may require initiation of treatment shortly after birth. As has been observed for Krabbe disease, the result of such cases is frustration both for the affected families and for follow-up care providers.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper, three LSDs were evaluated -Pompe disease, Fabry disease, and Krabbe disease which fail to meet some of the critical Wilson and Jungner criteria and thus are not ready for inclusion in universal NBS panels. It was concluded that screening for these conditions should only be performed in the research context with institutional review board approval and parental permission [ 18 ].…”
Section: Lysosomal Storage Diseases By Tandem Mass Spectrometrymentioning
confidence: 99%
“…A number of studies have focused on the optimal approach for sensitive and specific NBS for MPS I [16][17][18][19], and several NBS pilot programs that include MPS I screening have recently begun [1,20,21]. However, discussions on including MPS I in NBS programs will raise ethical issues, including the drawbacks of early detection in patients with late-onset, attenuated phenotypes [22][23][24][25], that need to be addressed.…”
Section: Introductionmentioning
confidence: 99%